The Effectiveness of Tea Tree Oil and Eucalyptus Oil Aromaterapy for Toddlers with Common Cold - Maftuchah Maftuchah; Priskila Iris Christine; M Jamaluddin (JURNAL KEBIDANAN, 2020)
Common cold is a mild viral infection of the upper respiratory tract, nose, and throat. Common cold suffered by each toddler in Indonesia is predicted to occur three to six times a year, which means that a toddler may experience three to six times of coughs and colds every year. Common cold is also a symptom of Covid-19 whose early treatments used symptomatic and non-pharmacological therapy including tea tree oil and eucalyptus oil aromatherapy. Related to this, this paper reveals the effectiveness of tea tree oil and eucalyptus oil aromatherapy for the healing period of 1 to 2-year-old toddlers in T W Independent Midwifery Practice (IMP). This paper employs quasy experiment design with non-equivalent control group model. Sample includes 14 toddlers with the age of 1 to 2-year-old. Seven of them were given tea tree oil, while the rest were given eucalyptus oil aromatherapy with accidental sampling technique. Aromatherapy was given once a day for seven days. Findings showed that the healing period of the control and intervention group was four to five days and according to the Mann Whitney trial, p-value of 0,530 (0,05) was obtained. In conclusion, there is no difference between the healing period of common cold using tea tree oil and eucalyptus oil aromatherapy for 1 to 2-year-old toddlers in T W Independent Midwifery Practice (IMP). Tea tree oil and eucalyptus oil aromatherapy can be used to accelerate the healing period of common cold suffered by toddlers.